2017
DOI: 10.1098/rspb.2017.1502
|View full text |Cite
|
Sign up to set email alerts
|

Social disappointment explains chimpanzees' behaviour in the inequity aversion task

Abstract: Chimpanzees' refusal of less-preferred food when an experimenter has previously provided preferred food to a conspecific has been taken as evidence for a sense of fairness. Here, we present a novel hypothesis-the social disappointment hypothesis-according to which food refusals express chimpanzees' disappointment in the human experimenter for not rewarding them as well as they could have. We tested this hypothesis using a two-by-two design in which food was either distributed by an experimenter or a machine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 57 publications
4
47
0
Order By: Relevance
“…The children co-operated in several experimental setups, and it was shown that the common goal is so important that individual children who reached their goals early did not stop their actions until all the others had reached their goals. Similar behavior could not be observed in great apes (Tomasello 2008;Bohn et al 2016;Engelmann et al 2017).…”
Section: Humans and Their Ancestorssupporting
confidence: 65%
See 1 more Smart Citation
“…The children co-operated in several experimental setups, and it was shown that the common goal is so important that individual children who reached their goals early did not stop their actions until all the others had reached their goals. Similar behavior could not be observed in great apes (Tomasello 2008;Bohn et al 2016;Engelmann et al 2017).…”
Section: Humans and Their Ancestorssupporting
confidence: 65%
“…Although great apes understand many aspects of social interactions in their lifeworlds, including causal and intentional relationships, there is a crucial difference from human understanding: In contrast even with human infants, great apes cannot participate in shared intentionality or cooperative communication (Tomasello 2008;Bohn et al 2016;Engelmann et al 2017).…”
Section: Humans and Their Ancestorsmentioning
confidence: 99%
“…Generally, testing procedures involve two conspecifics facing a food distribution task that may potentially trigger phenomena such as inequity aversion (eg. Brosnan & de Waal, 2003; but see Engelmann, Clift, Herrmann, & Tomasello, 2017), no cost prosociality (eg. Horner, Carter, Suchak, & de Waal, 2011), food sharing (Silk, Brosnan, Henrich, Lambeth, & Shapiro, 2013) or reciprocity (eg.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, both forms can already be observed in 3 year old toddlers (Ulber et al, 2017). Inequity aversion has also been reported in a variety of primate species (reviewed in Talbot et al, 2016;Ulber et al, 2017; but see Engelmann et al, 2017), but only in the egocentric form (but see Brosnan et al, 2010).…”
Section: Social Norms I: Universal Biologically Anchored Contentsmentioning
confidence: 97%